EVALUTION OF UNILATERAL ELECTRO-CONVULSIVE THERAPY (A double blind study) - Chatterjee, S. B. (Medknow Publications, 1980)
A double blind study of one hundred twenty patients ( ninety schizophrenics and thirty depressives )—who were divided equally into three groups, who received either (a) bilateral ECT or (b) unilateral application of electrodes on non-dominant hemisphere or (c) unilateral on dominant hemisphere was conducted. The three groups were compared regarding efficacy of the therapy, effects on memory, speed of recovery from each shock session and lastly changes in the electro-encephalogram. It was found that all the three techniques were more or less equal in therapeutic efficacy. There was no significant difference between them in the speed of recovery, nor in the EEG changes. Only difference was that in the field of memory, unilateral non-dominant group showed significant improvement in the ‘immediate verbal recall’ component of memory in particular. Results have been discussed in view of the current literature on the subject.